Influence of Cryogenic Treatment on the Tribological Behaviour of AISI H21 Tool Steel - Dileep Korade; Kavuluri Venkata Ramana; Kirankumar Jagtap (Materials Research, 2018)
The aim of the present work was to find out the optimum cryosoaking duration of deep cryogenic treatment to reduce the wear rate. The AISI H21 hot work tool steel specimens were hardened at 1195 ºC, cryotreated at -185 ºC for 6 to 30 h, double tempered at 540 ºC and soft tempered at 100 ºC. The hardness, impact toughness, wear rate and microstructural characteristics of the cryotreated specimens were studied. Wear test parameters were optimized by using Taguchi technique. Analysis of variance and signal to noise ratio were carried out in order to find significant parameters affecting the dependent parameter. The results show that load is the most influencing parameter followed by sliding velocity and cryosoaking duration. The linear mathematical model has been developed for wear rate using a regression analysis technique which will be useful for predicting results for new experiments.